2012
DOI: 10.5333/kgfs.2012.32.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Suitability Classes for Italian Ryegrass (Lolium multiflorum Lam.) Using Soil and Climate Digital Database in Gangwon Province

Abstract: As a part of establishing suitability classification for forage production, use of the national soil and climate database was attempted for Italian ryegrass (Lolium multiflorum Lam., IRG) in Gangwon Province. The soil data base were from Heugtoram of the National Academy of Agricultural Science, and the climate data base were from the National Center for Agro-Meteorology, respectively. Soil physical properties including soil texture, drainage, slope available depth and surface rock contents, and soil chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…Kim et al (2012) developed a GISbased IRG suitability mapping system based on climatic and soil conditions and plant tolerance characteristics in Gangwon Province, South Korea, and reported that Yeongdong area in Gangwon Province was confirmed as the suitable cultivated region for IRG. Kim et al (2012) developed a GISbased IRG suitability mapping system based on climatic and soil conditions and plant tolerance characteristics in Gangwon Province, South Korea, and reported that Yeongdong area in Gangwon Province was confirmed as the suitable cultivated region for IRG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al (2012) developed a GISbased IRG suitability mapping system based on climatic and soil conditions and plant tolerance characteristics in Gangwon Province, South Korea, and reported that Yeongdong area in Gangwon Province was confirmed as the suitable cultivated region for IRG. Kim et al (2012) developed a GISbased IRG suitability mapping system based on climatic and soil conditions and plant tolerance characteristics in Gangwon Province, South Korea, and reported that Yeongdong area in Gangwon Province was confirmed as the suitable cultivated region for IRG.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies about the effects of climatic factors on IRG yield and suitability have been actively implemented in South Korea. Kim et al (2012) developed a GISbased IRG suitability mapping system based on climatic and soil conditions and plant tolerance characteristics in Gangwon Province, South Korea, and reported that Yeongdong area in Gangwon Province was confirmed as the suitable cultivated region for IRG. Furthermore, Kim et al (2014) explored the climate effects on IRG yield via structural equation model and found that there was a weather effect on IRG yield.…”
Section: Introductionmentioning
confidence: 99%
“…According to KSIS, the DC of the upland was distributed to well (2) or moderately well (3) while that of the paddy was distributed to somewhat poorly (4) or poorly (5). In this study, only soil physical properties were considered because soil chemical properties could not be supplied from soil information system due to changeable feature (Kim et al, 2013).…”
Section: Ties Of Grasses and Forage Crops Operated By National Agricumentioning
confidence: 99%
“…Potential areas for apple cultivation have also been investigated [10,11]. Moreover, suitable areas for growing Italian ryegrass have been predicted in Gangwon-do [12] using a spatial distribution model [13]. Because climate change affects crops and their cultivation area [14], suitable growing areas have been identified for southern-type garlic [15], black raspberry [16], and teff and barley [17].…”
Section: Introductionmentioning
confidence: 99%